Detecting and Mitigating Smart Insider Jamming Attacks in MANETs Using Reputation-Based Coalition Game - Ashraf Al Sharah; Taiwo Oyedare; Sachin Shetty (Journal of Computer Networks and Communications)
Security in mobile ad hoc networks (MANETs) is challenging due to the ability of adversaries to gather necessary intelligence to launch insider jamming attacks. The solutions to prevent external attacks on MANET are not applicable for defense against insider jamming attacks. There is a need for a formal framework to characterize the information required by adversaries to launch insider jamming attacks. In this paper, we propose a novel reputation-based coalition game in MANETs to detect and mitigate insider jamming attacks. Since there is no centralized controller in MANETs, the nodes rely heavily on availability of transmission rates and a reputation for each individual node in the coalition to detect the presence of internal jamming node. The nodes will form a stable grand coalition in order to make a strategic security defense decision, maintain the grand coalition based on node reputation, and exclude any malicious node based on reputation value. Simulation results show that our approach provides a framework to quantify information needed by adversaries to launch insider attacks. The proposed approach will improve MANET’s defense against insider attacks, while also reducing incorrect classification of legitimate nodes as jammers.